2019
DOI: 10.3126/ajms.v10i6.25878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood groups in patients with anti TPO positive

Abstract: Background: In studies, ABO blood group system has been shown to be associated with type 2 diabetes mellitus, chronic renal failure, gestational diabetes mellitus, postpartum depression, coronary artery disease, Crohn’s disease as well as various cancer types such as stomach, breast, skin cancers and rheumatologic diseases. Aims and Objective: The relationship between anti TPO positivity and ABO blood group system is aimed to be investigated by using blood groups which are the product of genetic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Blood group antigens are genetically encoded and these antigens may be a predisposing factor for some diseases and a protective factor for some others. Studies have shown that some rheumatological diseases, viral infections such as Norwalk virus and Hepatitis B, and some types of cancer are associated with the ABO blood group 5‐8 . In addition, it has been found that the rate of infection with SARS coronavirus is lower in blood group O 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood group antigens are genetically encoded and these antigens may be a predisposing factor for some diseases and a protective factor for some others. Studies have shown that some rheumatological diseases, viral infections such as Norwalk virus and Hepatitis B, and some types of cancer are associated with the ABO blood group 5‐8 . In addition, it has been found that the rate of infection with SARS coronavirus is lower in blood group O 9…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that some rheumatological diseases, viral infections such as Norwalk virus and Hepatitis B, and some types of cancer are associated with the ABO blood group. [5][6][7][8] In addition, it has been found that the rate of infection with SARS coronavirus is lower in blood group O. 9 By examining the relationship of the human blood group with virus infection, it is possible to determine the susceptibility of people with different blood types to viruses.…”
mentioning
confidence: 99%
“…Studies have shown that some rheumatological diseases, viral infections such as Norwalk virus and Hepatitis B, and some types of cancer are associated with the ABO blood group. [5][6][7][8] In addition, it has been found that the rate of infection with SARS coronavirus is lower in blood group O. 9 By examining the relationship of the human blood group with virus infection, it is possible to determine the susceptibility of people with different blood types to viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been published to date on the relationship between blood groups and diseases. [29][30][31][32] These studies include hepatitis B, hepatitis C, HIV, West Nile Virus, SARS-CoV and SARS-CoV-2 viruses. [28,30,33] In all these studies raised an issue that some blood groups may be susceptible to viral infections and some groups may be protective.…”
Section: Discussionmentioning
confidence: 99%